Prevention of catheter-associated infection: effect of an intervention on the knowledge of intensivists - Campos Mota, Écila; de Oliveira, Adriana Cristina (O Mundo da Saúde, 2023)
Urinary tract infection is one of the most common problems during health care, especially in the intensive care unit, and is mostly associated with the use of a urinary catheter, contributing significantly to mortality, morbidity, and the cost of treatment. The objective of this study was to evaluate the effect of an educational intervention on the knowledge of intensive care professionals upon measures to prevent urinary tract infections associated with the use of a urinary catheter. This is a before-and-after intervention study, carried out in a ten-bed intensive care unit in a high-complexity hospital. Data collection included three moments: pre-intervention, intervention, and post-intervention, carried out between January 2018 and January 2019. In the pre- and post-intervention, an interview was carried out using a structured questionnaire. The intervention took place through a training session with active methodologies and practical demonstrations. There was a trend towards increased knowledge in all items evaluated for the prevention of urinary tract infections associated with the use of a urinary catheter, with significant differences (p<0.05) concerning hand hygiene, indications for catheter insertion bladder, barrier measures in the insertion technique, and prevention of this infection during manipulation and maintenance of the bladder catheter. The intervention provided an increase in the knowledge of professionals about prevention measures. However, gaps related to these practices were still being verified and long-term interventions should be conducted with a view to the improvement and safety of care.